2013
DOI: 10.1016/j.resuscitation.2012.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Does the number of rescuers affect the survival rate from out-of-hospital cardiac arrests? Two or more rescuers are not always better than one

Abstract: Review: An increased number of rescuers may improve the survival rate from out-of-hospital cardiac arrests (OHCAs). The majority of OHCAs occur at home and are handled by family members.Materials and Methods: Data from 5,078 OHCAs that were witnessed by citizens and unwitnessed by citizens or emergency medical technicians from January 2004 to March 2010 were prospectively collected. The number of rescuers was identified in 4,338OHCAs and was classified into two (single rescuer (N=2,468) and multiple rescuers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…In our previous study [17], the presence of multiple rescuers was associated with improved 1-Y survival after OHCAs; similarly, in the present study, the presence of multiple rescuers was independently associated with good-quality BCPR. Presumably, the presence of multiple bystanders increases the chances of bystander initiative from individuals who are able to provide good-quality CPR.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our previous study [17], the presence of multiple rescuers was associated with improved 1-Y survival after OHCAs; similarly, in the present study, the presence of multiple rescuers was independently associated with good-quality BCPR. Presumably, the presence of multiple bystanders increases the chances of bystander initiative from individuals who are able to provide good-quality CPR.…”
Section: Discussionsupporting
confidence: 85%
“…The time points of arrest recognition/witness and BCPR initiation were estimated by the EMTs by interviewing bystanders, as previously described [16]. Bystanders' relationship to the OHCA patient, bystander's age and gender of bystanders, bystanders' BLS training experience and total number of rescuers were also identified by the EMTs by interviewing bystanders, as previously described [17]. The time of dispatch-assisted initiation of BCPR following DA-CPR was identified by dispatch records.…”
Section: Patient Datamentioning
confidence: 99%
“…These data and the results of analysis for supplementary data in Ishikawa Prefecture (Supplementary Table 1) indicate that older family members, mostly aged couples are left at home during daytime. Because placing an emergency call is frequently delayed [19] and multiple rescuers are rarely present [21] at home, this environment may be more isolated from the emergency medical service system during daytime. Large questionnaire surveys have shown that elderly citizens are more reluctant to attend BLS courses [22] and perform BLS [23].…”
Section: Differences In Bystander Response Among the Three Groupsmentioning
confidence: 99%
“…Survival from sudden cardiac arrest in China is much lower than in many countries. Immediate bystander cardiopulmonary resuscitation (CPR) increases out-of-hospital cardiac arrest (OHCA) survival by twofold to threefold [5–7]. The chance of surviving OHCA falls by 7%–10% per minute without intervention [8].…”
Section: Introductionmentioning
confidence: 99%